Lemongrass (Cymbopogon flexuosus) productivity as affected by salinity of irrigation water, planting method and fertilizer doses on degraded calcareous soil in a semi-arid region of northwest India - DAGAR, J C; TOMAR, O S; MINHAS, P S; KUMAR, MUKESH (The Indian Journal of Agricultural Sciences, 2026)
Traditional cropping being non-viable with existing saline underground waters especially on the degraded calcareous soils of arid and semi-arid regions of India, these usually remain uncultivated. Salt tolerant and low water requiring medicinal and aromatic plants can provide for viable alternative to effectively utilize these lands. Thereby, different experiments were conducted during 2005-08 with lemongrass (Cymbopogon flexuosus (Steud.) Wats) so as to standardize cultivation techniques including optimal irrigation and fertilizer requirements, appropriate method of planting and promising salt-tolerant cultivars on a sandy loam calcareous degraded soil using saline water (ECiw 8.6 dS/m). The average fresh foliage yield was found to be 12.0-13.0, 6.7-8.3 and 9.1-9.8 Mg/ha, respectively, when irrigated with water of low salinity(ECiw 4.0 dS/m), high salinity (ECiw 8.6 dS/m) and alternately with two waters. There was increase in yield with increase of frequency of irrigation particularly during second year. Similarly, increased nitrogen and phosphorus doses could increase the yield but significant response was only during second year. Furrow planting followed by flat method of planting were superior. Amongst the cultivars tested, RRL 16 and OD 58 showed better performance followed by Praman and Krishna. The overall results indicated the possibilities of raising lemongrass on degraded calcareous soil using saline water up to EC 8.6 dS/m without build up of soil salinity if normal rainfall occurs once in 3-4 years.